(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2025)
Abstract. This article is devoted to the grammatical construction of collocations, and aims to analyze their importance in linguistics, their components and grammatical features. Collocations arise in natural combinations of different words, and these combinations play an important role in the coherent functioning of the language. The article analyzes the grammatical formation of collocations and their stylistic role.